Justice in Leadership - Robson, Angus (Journal of business ethics, 2026)
Although justice in organisations is well researched as a descriptive concept, there are few well-developed accounts of justice as a normative concept in organisational leadership. This study explores a Thomistic Aristotelian account of justice in leadership, in which justice is seen as a virtue of right relations and action, which enables leaders to recognise and honour their obligations towards others. Eight normative principles of just leadership are developed from this account, including the pursuit of the common good, protection of the rights of individuals and the importance of rules. A critical discussion of current theories of ethical leadership is offered in the light of the eight principles. Whilst some theories are compatible with this account of justice in leadership, some, such as authentic leadership, are less so. The practical implications of just leadership in business ethics are discussed and challenges are explored. A claim is made for justice as a gold standard for ethical leadership, which is capable of providing an answer to the question: ‘What is good leadership?’ This claim invites challenge from further research and critical engagement from other traditions of justice to develop and test the standard.